Experiences of Implementing Rooming-in Practice for First-Time Mothers in a Postpartum Care Center - Hsiao-Ling Wu; Der-Fa Lu; Pei-Kwei Tsay (SAGE Publishing, 2023)
Introduction Practices promoted by the Baby-Friendly Hospital Initiative have become a part of the current mainstream postpartum infant care. However, adherence to rooming-in practice by health-care facilities is lower than that of other steps under this initiative. Objective The aim of this study was to investigate the experiences in implementing the rooming-in policy among first-time mothers at a postpartum center. Methods The present study is a qualitative research conducted using the descriptive phenomenological method. This study was performed at a postpartum care center in Southern Taiwan between August 2018 and December 2018. Semi-structured interviews were conducted with 20 postpartum mothers during their postpartum care center stay. Results Based on interview data, this study identified three main themes about implementing full-time rooming-in experiences: (a) against the rule of taking plenty of rest during the postpartum period, (b) negative experiences and myths regarding implementing rooming-in experience, and (c) postpartum care centers service content affect first-time mothers' willingness to implement rooming-in. Conclusions In postpartum care centers, first-time mothers' willingness to implement full-time rooming-in significantly decreases due to the effects of the "doing-the-month" culture, postpartum physical recovery status, stress of the rooming-in experience, myths regarding rooming-in practice, trusting professional neonate care services more than own care, and attitude toward payment for services.